What are banks' actual capital targets? - Cyril Couaillier (European Central Bank (ECB), 2021)
How do banks set their target capital ratio? How do they adjust to reach it? This paper answers these questions using an original dataset of capital ratio targets directly announced to investors by European banks, materially improving data quality compared to usual estimated implicit target. It provides the following key lessons. First, targets are affected by capital requirements and a procyclical behavior consistent with market pressure. Second, banks do not distinguish between the different types of capital requirements for setting their targets, suggesting weak usability of the regulatory buffers. Third, the distance between actual CET1 ratio and the target is a valuable predictor of future balance-sheet adjustment, suggesting that banks actively drive their capital ratios toward their announced targets, through capital accumulation and portfolio rebalancing. Fourth, this adjustment occurs both above and below targets, but banks below target adjust faster, suggesting stronger pressure. These results provide important lessons for policymakers regarding the design of the prudential framework and the effectiveness of countercyclical policies.
Keywords: E51; E58; G21; G28; 330; Bank regulation; target capital structure; Bank credit